Обратная нелинейная задача гравиметрии на основе аналогов фильтров Винера–Калмана - Миненко, П.А. (Видавничий дім "Академперіодика" НАН України, 2008)
An iterative method of solution of a nonlinear inverse problem of gravimetry on the basis of the joint application of several cards of the measured field and several vectors of entry conditions for depths up to blocks of rocks in one iteration is developed. Examples of the interpretation of the gravitational field measured in the Western Krivbass are given.